2022
DOI: 10.1186/s13690-022-00786-6
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and determinants of postpartum family planning uptake among postpartum women in Western Ethiopia: a facility-based cross-sectional study

Abstract: Background Despite Ethiopia’s efforts to avail postpartum family planning (PPFP) services, the unmet need for family planning among postpartum women remains high. Therefore, this study is aimed to assess barriers and determinants of postpartum family-planning uptake among women visiting Maternal, Neonatal, and Child Health (MNCH) services in public health facilities of western Ethiopia. Methods A facility-based cross-sectional study design with a q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 16 publications
(26 reference statements)
2
6
1
Order By: Relevance
“…On the other hand, it could also be because most women have resumed their sexual activity and menses and feel they are at risk of unintended pregnancy [28,29]. Our findings may support previous studies indicating that the return of sexual activity and menstrual cycle following childbirth were the strongest predictors for adopting modern contraceptives in Ethiopia [19,30,31]. These findings underscore the importance of improving the integration of family planning counselling into relevant MCH services.…”
Section: Plos Global Public Healthsupporting
confidence: 85%
See 3 more Smart Citations
“…On the other hand, it could also be because most women have resumed their sexual activity and menses and feel they are at risk of unintended pregnancy [28,29]. Our findings may support previous studies indicating that the return of sexual activity and menstrual cycle following childbirth were the strongest predictors for adopting modern contraceptives in Ethiopia [19,30,31]. These findings underscore the importance of improving the integration of family planning counselling into relevant MCH services.…”
Section: Plos Global Public Healthsupporting
confidence: 85%
“…This is consistent with studies conducted in South Ethiopia [19] and Kenya [32]. However, other studies evaluating the effect of family planning counselling during ANC on postpartum modern contraceptive uptake have reported a positive association [18,30,31,33]. For example, a study conducted in Northern West Ethiopia indicated that family planning counselling during ANC was associated with increasing modern contraceptive uptake by six weeks postpartum [18].…”
Section: Plos Global Public Healthsupporting
confidence: 82%
See 2 more Smart Citations
“…[12][13][14] In addition to insufficient numbers of skilled care providers, poor organization of care processes, fragmented delivery of FP, routine maternal care, and a lack of a private counseling space for PPFP counseling are often barriers for postpartum women. [15][16][17] The aim of this study was to assess the combined effect of a package of interventions (creating a private counseling space near the postpartum ward and providing training for health care providers on the WHO decision tool kit and LACM) on the uptake and quality of PPFP services at Y12HMC, Addis Ababa, Ethiopia. the study used WHO decision tool kit for counseling clients.…”
Section: Effect Of Package Of Interventions On the Use And Quality Of...mentioning
confidence: 99%